Accessibility Barriers in Brazilian Government Mobile Applications: A Thematic Analysis of User Reviews - Sato, Mariana H. K.; R. Junior, Agnaldo C.; Leal, Gislaine C. L.; Coleti, Thiago Adriano; Guerino, Guilherme C.; Balancieri, Renato (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
This study analyzes accessibility barriers reported by users in reviews of three Brazilian government mobile applications (gov.br, Meu SUS Digital, and Carteira de Trabalho Digital), available on the Google Play Store. A qualitative thematic analysis was conducted on user evaluations. Two central themes emerged: issues in the implementation of accessibility features and the implicit expectation of a standardized user, particularly in facial biometrics. The results show that the mere presence of features does not ensure accessibility, highlighting the need for inclusive and user-centered design. The research contributes by providing empirical evidence based on users’ experience and by demonstrating the feasibility of reviews as a complementary source for analyzing accessibility.